Band gap tuning of layered III-Te materials - Olmos Asar, Jimena Anahí (2018)
Gallium telluride is a layered material with high photoresponse and is very promising for applications in optoelectronic devices such as photovoltaic cells or radiation detectors. We analyze how the properties of thin films of this material scale with its thickness and also study two other proposed materials with the same crystalline structure whose room-temperature stability we verify. We show that electronic band gaps up to 2.16 eV can be obtained by stacking up and/or applying perpendicular electric field to these III-Te monolayers. This form of band gap engineering may be promising for several technological applications.